Kualitas Fisik Daging Sapi Peranakan Simmental dengan Perlakuan Stimulasi Listrik dan Lama Pelayuan yang Berbeda - Rusdimansyah Rusdimansyah; Khasrad Khasrad (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2012)
This research was conducted to observe the influence of electric stimulation and chilling period on meat of Simmental cross. This experiment used factorial design with 5 blocks. The first factor was electric stimulation (with and without electric stimulation), the second factor was chilling period (0, 12 and 24 hours). Around 7.5 kg Simmental cross meat (Tricep brachii) from 5 head were used on this research. The observed variables were pH, cooking loss and tenderness. The results showed that there was no interaction of electric stimulation and chilling period (up to 24 hours) on all of observed variables. Electric stimulation treatment was significant improved tenderness of Simmental cross beef but it was not significant on pH and cooking loss. There was significant influenced of chilling period on pH, cooking loss and tenderness of Simmental cross beef.